Prediction of Digestible and Metabolizable Energy Content and Standardized Ileal Amino Acid Digestibility in Wheat Shorts and Red Dog for Growing Pigs - Huang, Q. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
Two experiments were conducted to evaluate the effects of chemical composition of wheat shorts and red dog on energy and amino acid digestibility in growing pigs and to establish prediction models to estimate their digestible (DE) and metabolizable (ME) energy content and as well as their standardized ileal digestible (SID) amino acid content. For Exp. 1, sixteen diets were fed to thirty-two growing pigs according to a completely randomized design during three successive periods. The basal diet was based on corn and soybean meal while the other fifteen diets contained 28.8% wheat shorts (N = 7) or red dog (N = 8), added at the expense of corn and soybean meal. Over the three periods, each diet was fed to six pigs with each diet being fed to two pigs during each period. The apparent total tract digestibility (ATTD) of energy in wheat shorts and red dog averaged 75.1 and 87.9%. The DE values of wheat shorts and red dog averaged 13.8 MJ/kg (range 13.1 to 15.0 MJ/kg) and 15.1 MJ/kg (range 13.3 to 16.6 MJ/kg) of dry matter, respectively. For Exp. 2, twelve growing pigs were allotted to two 6×6 Latin Square Designs with six periods. Ten of the diets were formulated based on 60% wheat shorts or red dog and the remaining two diets were nitrogen-free diets based on cornstarch and sucrose. Chromic oxide (0.3%) was used as an indigestible marker in all diets. There were no differences (p>0.05) in SID values for the amino acids in wheat shorts and red dog except for lysine and methionine. Apparent ileal digestibility (AID) and SID values for lysine in different sources of wheat shorts or red dog, which averaged 78.1 and 87.8%, showed more variation than either methionine or tryptophan. A stepwise regression was performed to establish DE, ME and amino acid digestibility prediction models. Data indicated that fiber content and amino acid concentrations were good indicators to predict energy values and amino acid digestibility, respectively. The present study confirms the large variation in the energy content and amino acid digestibility in wheat shorts and red dog, and describes the factors that influence this variation and presents equations based on chemical composition that could probably be used to predict the DE and ME values as well as the amino acid digestibility of wheat shorts and red dog.